Analisis Faktor – Faktor Yang Mempengaruhi Keputusan Konsumen Dalam Memilih Belanja Di Alfa Mart Curup - Muhammad Istan (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This study are to investigate the influence of cultural factors, social factors, personal factors and psychological factors on purchase decision in Alfa MartCurup. Analysis using multiple linear regression, F test, t test, test the coefficient of determination (R2). Multiple linear regression analysis showed that all variables figures obtained positive coefficient. The test results (F) indicates that the variable personal factors, social factor, cultural factors, psychological factor, and price factors together influence the purchasing decisions in Alfa Mart Curup. T test results showed that the variables of individual factors and psychological factors significantly influence purchasing decisions while variable cultural factors and social factors do not significantly influence the purchasing decision. To test the R2 (coefficient of determination) indicates that the variable cultural factors, social factors, personal factors and psychological factors were able to explain the variability of the variable of 21.7%. While the remaining 78.3% is explained by other variables outside the model. Keywords : Buying, Shoping, Consumer, Decision, Alfa Mart, personal factors, social factors, cultural factors,psychological factors and price factors.